Toward green tourism: the role of renewable energy for sustainable development in developing nations - Guo, Yang; Chai, Yi (Frontiers in Sustainable Tourism, 2025)
Sustainable tourism (TOR) practices are essential for balancing economic growth and environmental conservation, enabling economies to protect natural resources while fostering socio-economic development. In the BIMSTEC region, where tourism is a significant economic driver, understanding the interplay between tourism and renewable energy (RE) is critical for achieving sustainable development. This study examines the influence of TOR and RE on environmental quality, measured through the load capacity factor (LCF), in BIMSTEC countries. It also explores the interaction between TOR and RE to evaluate their combined impact on environmental sustainability. Using panel data from 2000 to 2022, the study employs advanced econometric techniques, including the cross-sectional autoregressive distributed lag (CS-ARDL) and augmented mean group (AMG) methodologies, to assess long-term relationships and robustness. Wavelet coherence analysis further examines time-frequency correlations between TOR and environmental quality. The results reveal that while TOR alone negatively impacts environmental quality, RE significantly enhances it, with a 1% increase in RE leading to a 0.04% improvement in LCF. The interaction term TOR*RE demonstrates a positive synergy, mitigating the adverse effects of tourism on the environment. The wavelet analysis highlights an inverse relationship between TOR and environmental quality over time, reinforcing the need for sustainable practices in the tourism sector. The findings emphasize the importance of integrating renewable energy into tourism policies to reduce air pollution and climate change impacts. Policymakers in BIMSTEC countries should focus on financial development and establishing sustainable tourism-related industries to address socio-economic and environmental challenges. This study provides actionable insights to promote environmentally sustainable tourism while supporting economic growth in the BIMSTEC region.